ANALYSIS OF TRANSACTION AUTHORIZATION FOR CREDIT CARD MASTER CARD HOLDERS - Alam Surawijaya; Elly Agustina. Skom, Elly Agustina. Skom (Jurnal Sistem Informasi, 1998)
The credit card is a kind of payment in lieu of cash has a bright prospect in the future,because with the risk of carrying cash large enough in terms of both security and theamount of cash required at certain moments.With so many banks are Mastercard credit card issuer, then Mastercard create acommunication network that is designed to serve all requests authorization from eachmember. Some of the benefits gained from the existence of this system are rapidlyincreasing the authorization process manager and the low value of the cost incurredby each card issuer.